2021
DOI: 10.1155/2021/8816540
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Flow Characteristics and Lane Use Strategies for Connected and Automated Vehicles in Mixed Traffic Conditions

Abstract: Managed lanes, such as a dedicated lane for connected and automated vehicles (CAVs), can provide not only technological accommodation but also desired market incentives for road users to adopt CAVs in the near future. In this paper, we investigate traffic flow characteristics with two configurations of the managed lane across different market penetration rates and quantify the benefits from the perspectives of lane-level headway distribution, fuel consumption, communication density, and overall network perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Some studies have suggested lower values for CAVs than for HDVs [22,23], whereas others have considered higher values [15,19,29]. Furthermore, others have maintained the same behavioural pattern [1,18,24]. Karjanto et al [3] explained that the corresponding value should be related to the driving style.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested lower values for CAVs than for HDVs [22,23], whereas others have considered higher values [15,19,29]. Furthermore, others have maintained the same behavioural pattern [1,18,24]. Karjanto et al [3] explained that the corresponding value should be related to the driving style.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Connected and autonomous vehicles (CAVs) fundamentally differ from human-driven vehicles (HDVs) in terms of their operational behaviour. CAVs can be adjusted to minimise emissions, improve fuel savings, and harmonise traffic flow due to their shorter reaction times [1][2][3][4][5]. Additionally, they are expected to change travel behaviour by generating new demand for very young, elderly, or disabled individuals, being utilized for freight transport, and impacting parking and ride-sharing patterns, thereby affecting the total vehicle miles travelled [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering that unreasonable ROW management can decrease the capacity, the interaction between mixed traffic flow (MTF) and transportation infrastructure management should be carefully considered. In several studies, the MTF capacity has been investigated using methods such as analytical modeling [21,33] and simulation [34,35] as well as empirical approaches [15,36]. These studies have formed a consensus that as the MPR of AVs and CAVs increases, the MTF capacity significantly increases.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing research assumed that there are two types of MTF: HDVs with AVs and HDVs with CAVs. It also did not sufficiently consider the complexity of heterogeneous traffic flow [24,30,32,36,37]. In fact, AVs and CAVs exhibit different characteristics that should be considered separately, because a CAV will generate much lower headway than that generated by an AV when forming a platoon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Talebpour et al evaluated three strategies and found that the throughput can be significantly improved at penetration rates of more than 50% for a two-lane highway and 30% for a four-lane highway [25]. However, the deployment of dedicated lanes can also cause a waste of road resources and worsen traffic conditions when the CAV penetration rate is low [26,27]. Hence, it may be best for dedicated lanes to be gradually deployed with an increase in CAV market penetration [28,29].…”
mentioning
confidence: 99%